2021
DOI: 10.33180/infmidem2020.405
|View full text |Cite
|
Sign up to set email alerts
|

Multiband Stepped Antenna for Wireless Communication Applications

Abstract: In this paper, a novel design of a coplanar waveguide fed (CPW) triple-band antenna is introduced. An ultra-wideband (UWB) characteristic is achieved by the initial design through the cut of a stepped shape from the lower part of the initial radiating patch and through the use of a truncated ground plan. To avoid the effects of the electromagnetic interferences with some coexisting wireless communication systems, a transition from the UWB to multiband function is assured by etching a simple circular ring insid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…8 indicates that the fabricated prototype operates in a super UWB extending from 1.95 GHz to upper than 20 GHz (>164.46 %) which is wider than the reserved UWB frequency band of 110 % (3.1-10.6 GHz). The simulated co-polar and [12,13]. Because of the extramodes at upper frequencies, it is observed that the magnitude of the cross-polar in the two planes augments with augmenting the frequency, also this augmentation can be attributed to the excitation of higher-order mode [14].…”
mentioning
confidence: 93%
“…8 indicates that the fabricated prototype operates in a super UWB extending from 1.95 GHz to upper than 20 GHz (>164.46 %) which is wider than the reserved UWB frequency band of 110 % (3.1-10.6 GHz). The simulated co-polar and [12,13]. Because of the extramodes at upper frequencies, it is observed that the magnitude of the cross-polar in the two planes augments with augmenting the frequency, also this augmentation can be attributed to the excitation of higher-order mode [14].…”
mentioning
confidence: 93%